Decolonization of subjectivities and african renaissance : criticism and reform of modernity by Scholastique Mukasonga, Ngugi wa Thiong'o and Valentin-Yves Mudimbe - (:unkn) unknown (My University, 2019)
The institutionalization of postcolonial studies and the recent development of decolonial studies have highlighted the recognition that intellectuals from former colonized territories enjoy today. Among them, Ngugi wa Thiong'o and Valentin-Yves Mudimbe are respected figures whose writings, both theoretical and fictional, seek to resolve the crises generated by the colonial experience. Aware that this did not end with the wave of independence, they kept alive in their works the utopian desire, that of conceiving a new world where relations between peoples and individuals would be renegotiated, despite the disappointments of the postcolonial regimes. However, the 1994 genocide of the Tutsis in Rwanda could well have symbolized the failure of their epistemic detachment efforts with Western modernity. This consisted in the repetition, on the African continent, of a crime similar to the one that had pushed many intellectuals to want to break with the order of which the Shoah was the consequence. On the contrary, Scholastique Mukasonga's texts bear witness to the repetition of the imperative formulated by Ngugi wa Thiong'o and Valentin-Yves Mudimbe, namely the need to achieve a decolonization of subjectivities to initiate an African renaissance. The study of each of their trajectories aims to show the complementarity of these two processes in their works which, separately, open the way to multiple possible futures for humanity.
Keywords: African Research